Natural Drug-Loaded Bimetal-Substituted Hydroxyapatite-Polymeric Composite for Osteosarcoma-Affected Bone Repair - Wang, Yanjun; Yao, Yongfeng; Thirumurugan, Muthupandi; Prabakaran, Selvakani; Rajan, Mariappan; Wang, Kai (Frontiers in Cell and Developmental Biology, 2021)
Repairing segmental bone deformities after resection of dangerous bone tumors is a long-standing clinical issue. The study's main objective is to synthesize natural bioactive compounds loaded bimetal substituted hydroxyapatite (BM-HA)based composite for bone regeneration. The bimetal (Copper and Cadmium) substituted HA'swere prepared by the sol-gel method, reinforced with biocompatible polyacrylamide (BM-HA/PAA). Umbelliferone (UMB) drug was added to the BM-HA/PAA composite to enhance anticancer activity further. The composite's formation was confirmed by various physicochemical investigations such as FT-IR, XRD, SEM, EDAX, HR-TEM techniques. The bioactivity was assessed by immersing the sample in simulated body fluid for 1, 3, and 7 days. The zeta potential values of BM-HA/PAA and BM-HA/PAA/UMB/ are –36.4 mV and –49.4 mV, respectively. The in-vitro viability of the prepared composites was examined in Mesenchymal stem cells (MSCs). It shows the ability of the composite to produce osteogenic bone regeneration without any adverse effects. The composite can induce bone genes (Runx, OCN, and VEFG gene) BM-HA/PAA/UMB composite from the gene expression and PCR results Since the prepared bimetal substituted polyacrylamide reinforced HA composite is the potential ability for bone repair/regenerations.